The Role of Indigenous Languages in Sustainable Development in Kenya - Ondondo, Emily Ayieta (Science Publishing Group, 2020)
A developed nation is a knowledgeable nation in educational, social, political, economic and cultural spheres. For individuals to develop educationally, socially, politically, economically and culturally, they need to interact with government agencies that disseminate related policies. Effective interaction and communication of related policies occurs through language and effective communication is achieved through a language that the communicants understand best. Therefore, to achieve national development in all areas, in Kenya, indigenous languages become pertinent in effective communication of information related to national development goals. This is because leaders and stakeholders in these areas need to effectively communicate information pertaining to their goals to the people at the grassroots, majority of who use indigenous languages as their main and most times sole language of interaction. In addition, a number of development indices, such as, national cohesion, integration, unity, economic wellbeing and citizen participation are all linked to the use of indigenous languages that promote them. Therefore, indigenous languages seem significant in the overall development of a nation. However, these languages are least considered in the propagation of development issues, something which has been left for Kiswahili and English. Using a descriptive design, this study, therefore, provides rationale for suppressed use of indigenous languages in development issues, as well as justification for the overt use of these languages in development issues for sustainable development.
Keywords: Indigenous Languages; Sustainable Development; Effective Communication; Development Policies; Development Goals; National Cohesion